THE EFFECT OF SEVERAL TOOTHPAST ON THE GROWTH OF Streptococcus mutans - Nawaly, Hermanus; Pagaya, Joseph; Kaihena, Martha (Universitas Pattimura, 2020)
This study aims to determine the effect of several toothpastes on the growth of Streptococcus mutans which is the main cause of tooth decay. The study used 5 types of toothpaste, namely toothpaste A, toothpaste B, toothpaste C, toothpaste D, and toothpaste E. The antibacterial testing method used the diffusion method with the cup-plate technique. The significance level of each type of toothpaste was measured using a completely randomized design followed by a Tukey test to see differences in toothpaste treatment. The results showed that toothpaste A with active ingredients Monofluorophosphate Sodium 1.12%, Triclosan 0.3%, Calcium Glycerophosphate 0.13% had the largest average resistance zone of 27.3 mm. Whereas Toothpaste E with the active ingredient 0.08% Sodium Monofluorophosphate, 0.01% Sodium Fluoride has the smallest average resistance zone, which is 14.25 mm. The diameter of the ANOVA test zone of several types of barrier toothpaste against Streptococcus mutans at 95% confidence intervals showed that there was a significant difference.